Физика 2.1 (СО): электронный курс - Кравченко Н. С. Надежда Степановна; Лисичко Е. В. Елена Владимировна; Борисенко С. И. Сергей Иванович; Постникова Е. И. Екатерина Ивановна; Моржикова Ю. Б. Юлия Борисовна; Никитина Л. Н. Лариса Николаевна (Томск, TPU Moodle, 2015)
Заглавие с экрана